Indian communism :opposition, collaboration, and institutionalization - Mallick, Ross (Oxford University Press, 1994)
Though Communism has ceased to exist in Europe, it is still found in the Third World where conditions favouring revolutionary change persist. The history of the Indian Communist Movement is a significant illustration of how, despite losing its global status, Communism has survived in India, albeit in a different form. The difference lies primarily in the fact that this doctrine has been democratized.